1978
DOI: 10.1136/jcp.31.11.1102
|View full text |Cite
|
Sign up to set email alerts
|

Failure of factor VIII inhibitor bypassing activity (Feiba) to secure haemostasis in haemophilic patients with antibodies.

Abstract: SUMMARY Factor IX concentrates have been widely advocated in the treatment of haemophilic patients with factor VIII inhibitors. Five such patients were given the 'activated' factor IX concentrate-factor VIII inhibitor bypassing activity (Feiba)-for 14 separate bleeding episodes. In six of the episodes, including two with external blood loss, bleeding progressed in spite of treatment. In none of the other eight episodes was there a prompt response, and it was not possible to ascribe a definite therapeutic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 20 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…4,5,12,15,22,[25][26][27] This process is divided into 3 phases: exudative, where fibrin development occurs; proliferative, which is characterized by the occurrence of fibroblastic and capillary proliferation; and reparative, evidenced by collagen synthesis and osteogenesis. 1 Studies have demonstrated that fibrin exerts at least two functions on a wound repair: homeostasis and stimulus to the proliferation of perivascular fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,12,15,22,[25][26][27] This process is divided into 3 phases: exudative, where fibrin development occurs; proliferative, which is characterized by the occurrence of fibroblastic and capillary proliferation; and reparative, evidenced by collagen synthesis and osteogenesis. 1 Studies have demonstrated that fibrin exerts at least two functions on a wound repair: homeostasis and stimulus to the proliferation of perivascular fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,12,15,22,[25][26][27] The presence of antibodies against coagulation factors or against platelets (immunothrombocytopenia) may impair the possibility to correct the defect in some patients. 13,16 In patients that are prescribed oral anticoagulants, the correction of the coagulation defect may be hazardous.…”
Section: Introductionmentioning
confidence: 99%
“…With the treatment of 3 plasma volumes (the usually recommended daily treat ment, which for an average plasma volume of 2,500-3,000 ml takes around 5h effective treatment time) it may be expected to regularly reduce inhibitor levels of 60-70 BU/ ml to below 10 BU/ml. With plasma exchange, on the other hand, mostly 2 or more treatment days have been required to bring down inhibitor levels initially no higher than 20-60 BU/ml [10][11][12][13], With prompt extensive removal of inhib itor, bleedings should be manageable with controlled dos ing of factor Vili or IX, which is safer than depending or arbitrary administration of PCC:s or APCC:s [6] or the more recently introduced factor VIIa [28]. However, there is a limitation to the level that can be reduced to below 10 BU/ml within 1 day; in our estimation it is unlikely that patients with levels exceeding 200 BU/ml could reach a level below 10 BU/ml, even if treatment is extended to 5-6 plasma volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Initially these preparations were mostly re ported to have a high rate of success in controlling bleeding episodes [4,5], but some studies failed to confirm the he mostatic effect and indicated them to be less effective than factor VIII was in normally responsive hemophiliacs [6,7], Porcine factor VIII has been used with satisfactory results Since the preferred treatment for all hemophiliacs is the administration of human factor Vili or IX, removal of inhibitors has been tried prior to the infusion of factor preparations. Early attempts with plasma exchange sug gested that antibody removal contributed to the successful clinical outcome reported for some patients [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of factor Vila cannot be ignored, especially in preparations that have high factor VII clotting activity, which can be tested by the relatively simpler method of Seligsohn et al [137]. cessful use of these activated concentrates, some investigators [117,120] have noticed unsuccessful responses in their patients and bleeding could not be controlled. Among a few patients who were successfully treated by Stenbjerg and Jorgensen [146], the plasma of 1 patient was found resistant to factor IX concentrate in an in vitro study and 1 patient showed evidence of DIC.…”
Section: Tests For the Detection Of Potential Thrombogenicitymentioning
confidence: 99%